Dysbiosis of gut microbiota and decreased propionic acid associated with metabolic abnormality in Cushing’s syndrome - Zhang, Qin; Hu, Wen-mu; Deng, Yu-ling; Wan, Jin-jing; Wang, Yu-jun; Jin, Ping (Frontiers in Endocrinology, 2023)
Abstract Objective: Chronic hypercortisolism leads to a phenotype that resembles metabolic syndrome. We aimed to investigate the association between the gut microbiota and the metabolic abnormality in endogenous hypercortisolism (Cushing’s syndrome). Methods: A total of 23 patients with Cushing’s syndrome (18 female and 5 men, aged 47.24±12.99 years) and 30 age-, sex-and BMI-matched healthy controls (18 female and 12 men, aged 45.03±6.69 years) were consecutively recruited. The differences in gut microbiota and plasma short-chain fatty acids (SCFAs) concentrations between the Cushing’s syndrome patients and controls were analyzed by 16S rRNA sequencing and gas chromatography-mass spectrometry (GC-MS). Results: Compared to controls, the Simpson and Pielou_e index of α diversity were dramatically decreased in Cushing’s syndrome (P < 0.05). The gut microbiota community structure differed significantly between Cushing’s syndrome patients and controls. Compared to controls, the bacterial communities of the Cushing’s syndrome patients were enriched in Proteobacteria and Escherichia-Shigella, and depleted in Firmicutes, including Agathobacter, Blautia, Anaerostipes, Eubacterium_eligens_group, and Lachnospira. Spearman analysis demonstrated that HbA1c, SBP, DBP, and cortisol levels were significantly positively correlated with Proteobacteria and Escherichia-Shigella, whereas negatively correlated with Agathobacter, Blautia, Anaerostipes, Eubacterium_hallii_group, and Lachnospira, etc. Cushing’s syndrome patients also had a lower propionic acid concentration (0.1510.054 vs. 0.2050.032 µg/mL, P=0.039) than controls. Furthermore, the level of propionic acid was negatively correlated with systolic pressure and cortisol level (P<0.05). Conclusion: Gut microbiota dysbiosis and decreased propionic acid levels were observed in patients with Cushing’s syndrome; therefore, the gut microbiota may be a potential therapeutic intervention target to improve the hypercortisolism-related metabolic abnormality.